Acoustic-radio cooperative marine information network - Quansheng GUAN; Weiqi CHEN; Hua YU; Fangjiong CHEN; Fei JI (Dianxin kexue)
The transmissions of ocean information have to cross the water-air interface.In this case,the information transmission network architecture requires the efficient integration of the underwater acoustic network and the radio network.However,the performance of the underwater acoustic link lags far behind the radio link,and becomes a bottleneck that restricts the performance of marine information networks.An acoustic-radio cooperative marine information network was proposed,which exploited the cooperation of acoustic and radio links to improve network performance.After demonstrating the advantages of acoustic-radio cooperation through three application scenarios,the network architecture and protocols,as well as the challenges for the acoustic-radio cooperative maritime information network were discussed.Acoustic-radio cooperation was not only an effective method for realizing the integration of air-water networks,but also an important method for realizing the integration of network communications,computing,and storage in marine information networks.